Simmons, Betty. New Perlican Photograph of a man and woman holding together glasses in a yard. - Barrett, Terra (2011)
A photograph of Susie Smith and Gordon Burrage having a drink celebrating their birthdays. Susie is standing and Gordon is sitting. A bench with the name "Smith" has flowers on it in front of a house in the background.